Stunting: The Role of Posyandu Cadres in Handling Stunting - Agastya, I Gede Pande Devin (PROMOTOR, 2025)
Indonesia is still one of the countries with a fairly high prevalence of stunting. Stunting has a nutritional status definition described by the PB/U or TB/U index in anthropometric measurements, the assessment of the results using the Z-Score table is at a threshold of <-2 SD to -3 SD which is included in the stunted category (short) and a threshold of <-3 SD which is included in the severely stunted category (very short). The most common risk factors for stunting in Indonesia are maternal, child and environmental factors. Integrated health services have an important role in helping to prevent stunting. Posyandu cadres are required to have good knowledge regarding stunting in order to educate mothers and families, which are the most common risk factors for stunting. The level of knowledge of posyandu cadres about stunting varies so that it is necessary to screen and make efforts to improve the knowledge of posyandu cadres.